2020
DOI: 10.31234/osf.io/mvtd8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the English version of the Fear of COVID-19 Scale and its relationship with behavior change and political beliefs

Abstract: Background: The COVID-19 pandemic has many individuals around the world fearing for their lives. The constant news coverage, rapid transmission, and relatively high mortality rate, make fearfulness a natural response. To assess the fear of COVID-19, the Fear of COVID-19 Scale (FCV-19S) was developed. The primary aim of the present study is to conduct the first psychometric assessment and validation of the English version of the FCV-19S.Methods: Two samples were collected in New Zealand. Sample 1 comprised 1,62… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 6 publications
7
52
3
5
Order By: Relevance
“…Since we conducted our study, other studies have found that fear can motivate protective behaviors within the context of the COVID. For example, in a study of a representative sample in the UK, Harper et al [ 25 ] concluded that “Consistently, the only predictor of positive behavior change (e.g., social distancing, improved hand hygiene) was fear of COVID-19.” Similarly, Winter et al [ 26 ] concluded: “… there was a significant relationship between FCV-19S scores [a measure of fear] and adherence to the lockdown rules that were implemented in New Zealand.” Bashirian et al [ 27 ], working within the context of Protection Motivation Theory [ 28 ], found that fear was positively related to complying with COVID preventative behaviors among medical staff in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Since we conducted our study, other studies have found that fear can motivate protective behaviors within the context of the COVID. For example, in a study of a representative sample in the UK, Harper et al [ 25 ] concluded that “Consistently, the only predictor of positive behavior change (e.g., social distancing, improved hand hygiene) was fear of COVID-19.” Similarly, Winter et al [ 26 ] concluded: “… there was a significant relationship between FCV-19S scores [a measure of fear] and adherence to the lockdown rules that were implemented in New Zealand.” Bashirian et al [ 27 ], working within the context of Protection Motivation Theory [ 28 ], found that fear was positively related to complying with COVID preventative behaviors among medical staff in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological impact was assessed by the Kessler Psychological Distress Scale (K10) [16], fear was assessed by the Fear of COVID-19 scale (FCV-19S) [17], and coping strategies were assessed by the Brief Resilient Coping Scale (BRCS) [18]. K10 was found to be a valid and reliable tool, with wide applications in research and clinical practice [16,19,20]; FCV-19S was developed more recently in response to the global pandemic of COVID-19, which was validated and tested for reliability in a few recent studies [17,21,22]; validity and reliability had also been tested for BRCS in earlier studies [18,23,24]. K10 has 10 items and response to each item in the questionnaire was measured using a 5-point Likert scale (none, a little, sometimes, most of the time, all the time).…”
Section: Study Toolmentioning
confidence: 99%
“…Psychological impact was assessed by the Kessler Psychological Distress Scale (K10) [16], fear was assessed by the Fear of COVID-19 scale (FCV-19S) [17], and coping strategies were assessed by the Brief Resilient Coping Scale (BRCS) [18]. K10 was found to be a valid and reliable tool, with wide applications in research and clinical practice [16,19,20]; FCV-19S was developed more recently in response to the global pandemic of COVID-19, which was validated and tested for reliability in a few recent studies [17,21,22]; validity and reliability had also been tested for BRCS in earlier studies [18,23,24]. K10 has ten items and response to each item in the questionnaire was measured using a 5-point Likert scale (none, a little, sometimes, most of the time, all the time).…”
Section: Study Toolmentioning
confidence: 99%
“…All items were scored, and the total score categorised into low (score 10-15), moderate (score [16][17][18][19][20][21], high (score 22-29) and very high (score 30-50). FCV-19S has seven items and the response to each item was also measured using a 5-point Likert scale (strongly disagree, somewhat disagree, neither agree nor disagree, somewhat agree, strongly agree), with scores categorised into low (score 7-21) and high (score [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. BRCS has four items and responses were collected again using a 5-point Likert scale (does not describe me at all, does not describe me, neutral, describes me, describes me very well), with scores similarly categorised into low (score 4-13), medium (score 14-16) and high (score 17-20) resilient copers.…”
Section: Study Toolmentioning
confidence: 99%
See 1 more Smart Citation